Increasing The Learning Enthusiasm of Elementary School Students Using Numeracy Guess The Number Ok Yes Combined With Ice Breaking to Show The Profile Of Pancasila Students - Aslinar; Nengsih, Ade Wahyu Asririya (Indonesian Journal of Sport, Health and Physical Education Science, 2023)
The purpose of this research is to increase students' enthusiasm for learning in the learning process by using numeracy guessing numbers ok yes combined with ice breaking. The method used is PTK (Classroom Action Research) with two cycles. In cycle I, did not use numeracy guessing numbers ok yes ice breaking, while in cycle II in every lesson using numeracy guessing numbers ice breaking ok yes which makes children enthusiastic and eager to learn and there is also a critical thinking process in learning that is useful for distinguishing various kinds of numbers. The subjects in this study were grade 6 (six) elementary school students in Mukomuko Regency, totaling 15 students. The learning outcomes obtained in cycle I were 46%, while in cycle II 100% by using the numeracy guess the number ok yes ice breaking learning pattern. The conclusion of this study is that numeracy guessing numbers ok yes combined with ice breaking can increase students' enthusiasm for learning in the learning process which shows the profile of Pancasila students and can make students think more critically.